Cerebral embolism during edoxaban administration for venous thromboembolism in a patient with lung adenocarcinoma: A case report. Issue 12 (March 2019) - Nakao, Satoshi; Masuda, Takeshi; Sakamoto, Shinjiro; Yamaguchi, Kakuhiro; Horimasu, Yasushi; Miyamoto, Shintaro; Nakashima, Taku; Iwamoto, Hiroshi; Fujitaka, Kazunori; Hamada, Hironobu; Hattori, Noboru
Abstract: Rationale: The efficacy of direct oral anticoagulants (DOACs) in the treatment and prophylaxis of cancer-related venous thromboembolism (VTE) is reportedly similar to that of heparin. However, the effect of DOACs on the prophylaxis of cancer-related arterial thromboembolism (ATE) remains unclear. To our knowledge, we present the 1st case where cerebral ATE was encountered during edoxaban administration for VTE in a patient with lung adenocarcinoma. Patient concerns: In March 2017, a 63-year-old female was diagnosed with lung adenocarcinoma (cT2aN3M1b stage IVa) along with having asymptomatic VTE; thus, 60 mg/day edoxaban administration was initiated. In addition, 1st-line chemotherapy generated a partial antitumoral response. However, owing to lung cancer progression, a secondary treatment with pembrolizumab administration was initiated. The patient suddenly experienced aphasia 11 days after pembrolizumab administration. Diagnosis: The patient was diagnosed as multiple cerebral ATE using brain magnetic resonance imaging. However, VTE recurrence was not observed. Based on the findings of lung cancer progression and increased coagulation, cerebral ATE was diagnosed as Trousseau syndrome. Interventions: DOAC administration was switched to heparin administration. Outcomes: Coagulation profile normalized and aphasia improved without any further disease symptoms. Lessons: We considered that DOACs are effective for the treatment and prophylaxis of VTE but may be insufficient for ATE prevention. Therefore, DOACs should be replaced with heparin to prevent ATE when cancer and coagulation become uncontrollable with DOAC.